Effects of asymmetric modulations in convection - Melentyev, Anatoliy Borisovich; Tarunin, Yevgeniy Leonidovich (Computational Continuum Mechanics, 2012)
This study examines the effects of asymmetric gravity modulation in a horizontal layer and a closed cavity heated from below, and the effects of asymmetric rotational oscillations of a closed cavity heated from below. The critical modulation amplitude is obtained as a function of the asymmetry parameter for microgravity, and the limiting flow characteristics as a function of the asymmetry parameter. It is shown that the asymmetry of rotational oscillations of the closed cavity influences the critical amplitude and the bifurcation diagram.
Keywords: asymmetric oscillations; translational and rotational oscillations; heat convection